USING THE PISA FORMAT ASSIGNMENTS IN RUSSIAN LANGUAGE LESSONS AT AN UZBEK SCHOOL (Innovative Technologica: Methodical Research Journal, 2023)
The article discusses methodological work in schools with the Uzbek language of instruction using tasks in the "PISA" format as a means of improving the reading literacy of foreign-speaking students. A number of tasks based on the PISA technology are given.